(untitled) (Journal of Technology and Operations Management, 2022)
Waste trade, like those of other resources, has grown globally. The waste trade must be implemented in order to ensure environmental sustainability and the transition to a circular economy (CE). Waste trade, in the context of CE, serves as a basis for the development of circular business operations by facilitating end-of-life product management activities such as product return, reuse, recycling, and refurbishment. China is regarded as a global leader in recycling and solid waste disposal. Solid waste management is the process of reusing manufactured products to recover and reuse resources including plastics. However, the reassessment of the quality of traded recyclable materials has sparked a global waste governance dilemma. The goal of this study is to bring attention to the environmental consequences of plastic waste in a transition to a CE and the overview of China’s national sword policy prohibition law. Using a qualitative approach, this study will analyse, assess, and formulate the practices of the waste trade that is now practised in the business. Various types of waste and how they cause emissions, waste trade and CE, China’s national sword policy and the consequences of worldwide plastic trade on businesses and the environment will be discussed. Additionally, a few steps that should be addressed including appropriate waste management and public awareness are also discussed.